Extendable Goal Post / Noor Syzwani Sulaiman - Sulaiman, Noor Syzwani; Ibnuataillah, Muhammad Zayanie; Jaafar, Mohamad Hakimi; Mohd Puat, Nur Fadzilah; Salmi, Mohammad Hazwan (2021)
New product development, is the process of bringing a new original product idea to the market. This project is an attempt to know how the theories can be applied to a practical situation. As a student in UiTM Arau, it is a part of a learning for everybody to perform a case study project. So, for this purpose, we got the opportunity to do a research on company which has the potential to market the new goal post with multifunctional function that comes along with invented technologies. The project entails the company profile and its products. In the implementation phase we also want to demonstrate the creation of a multi-purpose goal post that involves the production of ideas and the filtering of ideas. The first part of the study, the problem has been faced by many users or athletes while using a normal goal post. The difficulty that emerges when dealing with this goal post is that it only has one feature. The methodology analysis has explained in this report. The new product development is the main important point that has been classified into a few process. They are research and development, idea generation, idea screening, product design and features, concept testing, build prototype, and test marketing. Lastly, before we can launch the new goal post we must get the confirmation of the product from the community. The online questionnaire has been used in order to get their opinion and feedback. This is very important to gain as many opinions because it can be used to improve our product before actual launching. The technologies are invented in this new product to make it more effective with high quality and also can fulfil the customers need.